Thermal and mechanical stability of lanthanide-containing glass-ceramic sealants for solid oxide fuel cells - Reddy, Allu Amarnath
Thermal stability of lanthanide (Ln = La, Nd, Gd, Yb) containing glass and glass-ceramics (GCs) was characterized for their application as sealants for solid oxide fuel cells (SOFCs). X-ray diffraction (XRD) in conjunction with the Rietveld-RIR and solid-state NMR techniques was employed to quantify the crystalline and amorphous fractions in the glasses sintered/heat treated at 850 degrees C in air for 1-1000 h. The structure and crystalline phase evolution of Ln containing aluminosilicate glasses depend markedly on the Ln(3+) cation field strength over both short and intermediate length scales. Along with diopside, Ln containing silicate apatites, with general formula Ln(9.33+2x)(Si1-xAlxO4)(6)O-2 (Ln = La, Nd and Gd; with x varying between 0 and 0.33), were observed in the GCs after the heat treatment periods of 1 to 1000 h at 850 degrees C, leading to moderately higher electrical conductivity. The substantial amount of the remaining glassy phase in Gd2O3-containing GC after 1000 h at 850 degrees C is likely to confer self-healing properties to this composition, in accord with the oxygen leakage measurements on thermal cycling. Si-29, Al-27 and B-11 magic-angle spinning (MAS) NMR spectra confirmed the results of the XRD RIR analysis. The values of Weibull characteristic strength and of average flexural strengths for all the GCs are higher than those reported for G-18 commercial glass (51 MPa), with Weibull modulus varying in the range 11.6-34.4 towards good mechanical reliability. Thermal shock resistance of model electrochemical cells made of yttria-stabilized zirconia (YSZ) was evaluated employing quenching from 800 degrees C in air and water. All the GC seals bonded well to YSZ and Sanergy HT metallic interconnects without gap formation. Suitable thermal expansion coefficient (9.7-11.1 x 10(-6) K-1), mechanical reliability, high electrical resistivity, strong adhesion to Sanergy HT interconnects and YSZ, and sufficient thermal shock resistance indicate good suitability of the lanthanide-containing sealants for SOFC applications.